Role of TRAK1 variants in epilepsy: genotype–phenotype analysis in a pediatric case of epilepsy with developmental disorder - Li, Ren-Ke; Xiong, Yu-Rong; Pan, Shu-Jing; Lei, Wen-Ting; Shu, Xiao-Mei; Shi, Xiao-Qi; Tian, Mao-Qiang (Frontiers in Molecular Neuroscience, 2024)
Purpose The TRAK1 gene is mapped to chromosome 3p22.1 and encodes trafficking protein kinesin binding 1. The aim of this study was to investigate the genotype–phenotype of TRAK1-associated epilepsy. Methods Trio-based whole-exome sequencing was performed on a cohort of 98 patients with epilepsy of unknown etiologies. Protein modeling and the VarCards database were used to predict the damaging effects of the variants. Detailed neurological phenotypes of all patients with epilepsy having TRAK1 variants were analyzed to assess the genotype–phenotype correlations. Results A novel TRAK1 compound heterozygous variant comprising variant c.835C > T, p.Arg279Cys and variant c.2560A > C, p.Lys854Gln was identified in one pediatric patient. Protein modeling and VarCards database analyses revealed that the variants were damaging. The patient received a diagnosis of early infantile epileptic spasms with a developmental disorder; he became seizure-free through valproate and adrenocorticotropic hormone treatment. Further results for six variants in 12 patients with epilepsy indicated that biallelic TRAK1 variants (including homozygous or compound heterozygous variants) were associated with epilepsy with developmental disorders. Among these patients, eight (67%) had epileptic spasms and seven (58%) were intractable to anti-seizure medicines. Moreover, eight patients experienced refractory status epilepticus, of which seven (88%) died in early life. To our knowledge, this is the first reported case of epilepsy caused by TRAK1 compound heterozygous variants. Conclusion Biallelic TRAK1 variants can cause epilepsy and developmental disorders. In these patients, seizures progress to status epilepticus, suggesting a high risk for poor outcomes and the requirement of early treatment.